Odpowiedzi

2010-01-27T08:05:32+01:00
X = |x|(cosa + isina)
y = |y|(cosb + isinb)
Wtedy:
arg(x) = a
arg(y) = b

xy =
= |x|(cosa + isina)|y|(cosb + isinb) =
= |x| |y| (cosa + isina) (cosb + isinb) =
= |xy| (cosa cosb + i i sina sina + i cosa sinb + i sina cosa) =
= |xy| (cosa cosb - sina sinb + i(sina cosb + sinb cosa)) =
...
Tutaj korzystamy z wzorów na sin i cos sumy argumentów:
sin(a+b) = sina cosb + sinb cosa
cos(a+b) = cosa cosb - sina sinb
...
= |xy| (cos(a+b) + isin(a+b))

czyli arg(xy) = a+b

Zatem arg(xy) = arg(x) + arg(y)